Perkembangan Ekonomi Islam dalam Prespektif Karl Marx - Moh. Abdur Rohman Wahid (Journal Khafi : Journal Of Islamic Studies, 2024)
Islam and Karl Marx are interesting themes in Indonesia. In addition to the fact that the majority of Indonesians are Muslim, there is also an economic gap or gap. This article aims to re-map the flow of thinking related to the relationship between Islam and Karl Marxs so that it can be seen in a more balanced way. The method in this research is descriptive qualitative with a historical approach. The results of the study state that Islam has a very different basis from Marx's thought, even though both of them want a just s ociety without class oppression. But Islam still recognizes the potential differences that exist in each human being. Whereas in Marx's thought, the difference between people in accumulating funds lies in the mastery of the factors of production.